2020
DOI: 10.3991/ijim.v14i02.11819
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Heutagogical Practices among Student Teachers: Its Pedagogical Affordances and Challenges

Abstract: The integration of Information and Communication Technology (ICT) in the classroom for learning is becoming important to improve student engagement and interaction.  This is in line with the educational transformation towards achieving Higher Education 4.0 in Malaysia. Education 4.0 (Edu 4.0) is in line with the Industrial Revolution 4.0 (4IR) and underpin the Malaysia Education Blueprint 2015-2025. There has been a recent surge in published studies on Mobile-Heutagogy (M-Heutagogy), with most studies has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this case, three works stood out, for presenting resources that make education possible anywhere. Kung-Teck et al (2020) focus on the use of mobile devices. In an era where our smartphones are practically an extension of our bodies, they have immense potential to become a teaching tool.…”
Section: Yearsmentioning
confidence: 99%
“…In this case, three works stood out, for presenting resources that make education possible anywhere. Kung-Teck et al (2020) focus on the use of mobile devices. In an era where our smartphones are practically an extension of our bodies, they have immense potential to become a teaching tool.…”
Section: Yearsmentioning
confidence: 99%
“…Besides, the term self-determination learning used by a few studies has also integrated technologies in the teaching and learning process. A few studies have been identified to use mobile heutagogy to refer to the learning approach used [3] [44] [47]. Thus, no matter which terms has been used, mobile technologies and applications will be integrated as support tools in 21stcentury learning.…”
Section: 1mentioning
confidence: 99%
“…Heutagogy design are divided into six elements namely, (i) explore, (ii) create, (iii) collaborate, (iv) connect (v) share, and (vi) reflect (Blaschke & Hase, 2016). M-Heutagogy has been identified to be extended to the heutagogy approach (Wong et al, 2020). M-Heutagogy is suitable for 21st-century learning and in line with Education 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The terms M-Heutagogy came when academicians applied self-determined learning with any mobile applications and technologies to achieve learning objectives (Narayan & Herrington, 2014). M-Heutagogy has been identified to promote student agency, creating curiosity to learn new skills, and capability in determining their own learning (Wong et al, 2020). Several studies have begun to focus on technology to achieve educational transformation (Chan et al, 2018;Yusoff et al, 2018;Ayub, 2018;Kedin et al, 2018;Malek, 2017;Wahi & Idris, 2017).…”
Section: Introductionmentioning
confidence: 99%